2020
DOI: 10.1002/jgh3.12468
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum albumin and cognitive dysfunction in hepatic encephalopathy: An exploratory data analysis

Abstract: Background and AimBecause covert hepatic encephalopathy (CHE) has been shown to affect the prognosis of cirrhotic patients, early diagnosis of hepatic encephalopathy (HE) is a prerequisite for the preservation of patients' quality of life and for prophylaxis of overt HE. The aim of this study was to identify a clinical parameter to predict impairment of cognitive function in cirrhotic patients with early‐stage HE.MethodsWe investigated the data from 172 patients with cirrhotic or idiopathic portosystemic shunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
(55 reference statements)
3
2
0
1
Order By: Relevance
“…These results, which suggest the usefulness of the easy-to-use scoring model consisting of only blood biochemical parameters for CHE screening, have meaningful clinical implications for the management of patients with cirrhosis. These results also corroborate those of previous studies that reported an association between CHE and albumin or ammonia levels [ 16 , 25 , 28 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…These results, which suggest the usefulness of the easy-to-use scoring model consisting of only blood biochemical parameters for CHE screening, have meaningful clinical implications for the management of patients with cirrhosis. These results also corroborate those of previous studies that reported an association between CHE and albumin or ammonia levels [ 16 , 25 , 28 30 ].…”
Section: Discussionsupporting
confidence: 92%
“…According to our observed results, decreased albumin level in LPS-induced group was followed by increased ammonia, ALP, AST, and ALT level when compared with the control group (I). In accordance with our results, decreased serum albumin as a drawback of neuroinflammatory AD-type progression may results in server liver dysfunctions due to systemic malnutrition inflammatory syndrome (Kaji et al 2021 ; Llewellyn et al 2010a ; Cattin et al 1997a ). Meanwhile, increased Aβ serum level associated with increased cholesterol, triglycerides, and inflammatory cytokines serum levels in addition to decreased albumin level directly resulted in cardiac dysfunction illustrated in the form of increased heart rate, troponin I, CK-MB, LDH, ALT, and AST serum levels as illustrated in Fig.…”
Section: Discussionsupporting
confidence: 92%
“…При МПЭ отсутствуют явные клинические проявления, поэтому ее можно диагностировать только с помощью нейропсихологических или психометрических тестов [4]. МПЭ также может проявляться как недавние падения (40% в течение предыдущего года для тех, у кого диагностирована МПЭ, по сравнению с 12,9% для лиц без МПЭ), а также нарушением качества сна [5,6]. Помимо этого, наличие МПЭ у пациентов с ЦП имеет более высокий однолетний риск автомобильных аварий (17% из 97 пациентов с МПЭ против 3% из 70 лиц без МПЭ) [7].…”
Section: Introductionunclassified